A TEXTUAL ANALYSIS ON POWER DISTRIBUTION IN THE CLAUSES OF NEW INPUTS OF NATIONAL EDUCATION POLICY DRAFT IN INDIA - Muhammad Dzia Ul Haq (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Power is something that is useful to make things better or even worse. Those who have more power might be able to change or create something as they wish to be. The revamped proposal on the national education policy in India structured by the Ministry of Human Resource Development in 2016 becomes one example of how the power can be distributed through a national policy to instruct how the Indian education system should be, especially for a pre-primary student. The research tries to reveal the power distribution among Indian Governmental Institutions by using a descriptive qualitative research design with a textual analysis of Systemic Functional Linguistics (SFL) approach, concerning MOOD framework using MOOD elements Adjuncts and the Modality formed by Halliday (2004). The input on the New National Education Policy draft that is assessed is the one that is related to the pre-primary student by pointing out the MOOD Framework and Modality to see different power representations distributed by the Ministry of Human Resource Development to other institutions. Besides, this research will also reveal which excerpts have the most powerful representation.